Nanotechnology in textile and apparel research – an overview of technologies and processes. Issue 12 (1st December 2020) - Krifa, Mourad; Prichard, Cambry
Abstract: The potential of nanotechnology innovation in the textile industry is vast and promising. Major breakthroughs in novel nano-based textile finishing have been documented over the last two decades. In this report, we present an overview of nanotechnology developments highlighted in the research literature relevant to textile materials. The functions discussed span a broad array including self-cleaning, electrical conductivity, antibacterial potency, thermal stability and flame retardancy, thermal regulation, and selective permeability/adsorption. We review both particulate and fibrous structures proposed to impart those functionalities at the nanoscale. Among the most notable particulate structures, we discuss carbon nanotubes (CNTs), nanodiamonds, nanoclay, diverse metal nanoparticles such as silver and titanium dioxide (TiO2 ), and an array of bio-based nanomaterials including cellulose nanocrystals and chitosan. We then review the main approaches available to process nanofibers and discuss characteristics relevant to textile and apparel applications.